MODERN VIEW OF WORLD CITIES - Тўхтабоева Д. Э. (TARIXIY TADQIQOTLAR, 2025)
This article discusses the positive and negative impact that the modernization of the world’s cities has on people’s lives, affecting their appearance, naming, and function.